A proposed green tax reform for Cyprus and its co-benefits for urban sustainability - Zachariadis, Theodoros (My University, 2019)
Cyprus faces serious environmental challenges, which may be exacerbated in future due to climate change, and has specific obligations to reduce greenhouse gas emissions and waste production and use water more efficiently. This chapter formulates a proposal for a fiscally neutral green tax reform, which would facilitate the transition to a low-carbon, resource-efficient economy. We propose the gradual implementation of a carbon tax in sectors which are not subject to the EU Emissions Trading System; a water scarcity charge; and a landfill tax for waste that is disposed of in landfill. We assess the fiscal effects and environmental benefits of these taxes in the medium and long run, and evaluate the effects of the reform on social equity and competitiveness. We also assess the co-benefits of this reform for urban sustainability by calculating changes in air pollutant emissions and the associated reduction in pollution costs.
Keywords: Greenhouse gas emissions; Waste production